2017
DOI: 10.1002/ijc.30732
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers and cancer: CRP and suPAR as markers of incident cancer in patients with serious nonspecific symptoms and signs of cancer

Abstract: In Denmark, patients with serious nonspecific symptoms and signs of cancer (NSSC) are referred to the diagnostic outpatient clinics (DOCs) where an accelerated cancer diagnostic program is initiated. Various immunological and inflammatory biomarkers have been associated with cancer, including soluble urokinase plasminogen activator receptor (suPAR) and the pattern recognition receptors (PRRs) pentraxin‐3, mannose‐binding lectin, ficolin‐1, ficolin‐2 and ficolin‐3. We aimed to evaluate these biomarkers and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 56 publications
5
33
0
Order By: Relevance
“…The normal values are indicative of the absence of any discrepancy in hematopoietic as well as in immune functioning (18). The findings are in accordance with previous studies conducted to find the association between elevated levels of biomarkers and several organ-specific malignancies (26)(27)(28). Proteins (matrix metalloproteinase-7 and matrix metalloproteinase-12) are generally related to tumor growth and contribute to sustained proliferation and invasion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The normal values are indicative of the absence of any discrepancy in hematopoietic as well as in immune functioning (18). The findings are in accordance with previous studies conducted to find the association between elevated levels of biomarkers and several organ-specific malignancies (26)(27)(28). Proteins (matrix metalloproteinase-7 and matrix metalloproteinase-12) are generally related to tumor growth and contribute to sustained proliferation and invasion.…”
Section: Discussionsupporting
confidence: 92%
“…Proteins (matrix metalloproteinase-7 and matrix metalloproteinase-12) are generally related to tumor growth and contribute to sustained proliferation and invasion. CRP has been extensively studied as a biomarker of malignancies (26,29) and is supposed to support the tumor microenvironment by inducing tumor-promoting inflammation (30). Similarly, in canines, elevated levels of CRP have consistently been attributed to increased tumor progression and poor prognosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…M-ficolin is produced by PLOS ONE neutrophils and monocytes [45] and increased levels might therefore suggest ongoing inflammation. MBL and MASP-2 concentrations did not differ between cancer patients and healthy individuals, which is in accordance with previous studies by Rasmussen et al and Swierzko et al [43,46,47]. However, other previous studies reported increased concentrations of MBL and MASP-2 and increased MBL/MASP activity in cancer patients [12,13,31,48].…”
Section: Discussionsupporting
confidence: 91%
“…A previous study found threefold increases in H-ficolin levels in ovarian cancer patients suggesting this protein could be a potential biomarker for cancer [42]. However, a recent study by Rasmussen et al did not find increased H-ficolin levels in patients with various types of cancer [43]. The decrease in MAp44 in the present study is consistent with earlier findings in colorectal cancer patients [14].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, CRP is associated with the activity of infiltrated immune cells, including dendritic cells, T cells, and natural killer cells [72,73]. Many studies have shown that CRP is an independent biomarker for predicting prognostic outcome in various cancers [74][75][76]. The serum albumin level is used as a biomarker to evaluate liver function and nutritional status.…”
Section: Discussionmentioning
confidence: 99%